Efficient hydrogen storage in KCaF3 using GGA and HSE approach. (29th January 2023) - Fatima, Seerat; Rizwan, Muhammad; Naeem Ullah, Hafiz Muhammad; Ali, Syed Shahbaz; Naeem, Hamza; Usman, Zahid
Abstract: Being a renewable and sustainable energy carrier, hydrogen energy has garnered great interest having some technical barriers related to storage aspects. Hydride materials exhibit potential hydrogen storage capacities efficiently and safely. The current study has been performed in the framework of density functional theory to examine structural and optoelectronic properties of KCa F 3 − x H x (x = 0, 0.6, 1.2, 1.8, 2.4, and 3) compounds to understand their contribution about hydrogen storage. The mechanical stability of these compounds with elastic constants and negative formation enthalpies suggests these materials are stable and synthesizable. Insertion of impurity into pristine material led to an increase in optimized lattice parameter from 4.31 to 4.48 A ˙ where no previous study is available to compare lattice constants other than pristine KCa F 3 that is well consistent with existing literature. Computed and plotted results of plastic properties for different H-inclusions manifestly depict a decrease in elastic moduli, anisotropic and brittle nature of all studied materials. The density of states and band diagrams were drawn utilizing both GGA and HSE03 formalisms, where observations manifest not only an upsurge in bandgap but also shifting from indirect to direct nature. Two effects Burstein -Moss shift and bandgap renormalization were explored to investigate the shifting of absorption edge toward the valence band that results in bandgap narrowing. Optical parameters were also well explained within the photon energy range of 0–35eV. Startling results of absorption spectra reveal prominent redshift increases in the UV region. Among all H- insertions high value of the static refractive index (n (0) = 3.77) and dielectric function with minimum absorption losses possess KCa H 3 only appropriate material for storage aspects. Also, enhancement in optical properties suggests a new end material (KCa H 3 ) curious for optoelectronic devices. Moreover, H-incorporation has improved hydrogen storage characteristics up to a capacity of 3.6 wt% with the challenge of high desorption temperature whose improvement will play a vital role in hydrogen uptake mechanism and will enlighten future studies to make it useful for practical and transportation applications. Highlights: Hydrogen storage characteristics were improved via H-inclusion. Band engineering was performed utilizing both GGA and HSE03 formalisms. Redshift of energy states was noticed for all studied materials. Direct bandgap was achieved mainly for a new end material KCa H 3 . Brittle nature is observed for all substituted materials.